Method for preparing high-uniformity iron phosphate and lithium iron phosphate from iron-containing waste residues
Through efficient mass transfer technology and multi-step treatment, high-uniformity iron phosphate and lithium iron phosphate are prepared using iron-containing waste slag, which solves the problem of unstable product performance in the prior art, and realizes high-performance lithium iron phosphate preparation, which is suitable for commercial applications.
Patent Information
- Application Number
- CN202411926764.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-18
AI Technical Summary
In the prior art, the method of preparing lithium iron phosphate using iron-containing waste slag has uneven morphology and large particle size, resulting in long diffusion paths of lithium ions and limited capacity and performance, especially high-magnification attenuation, and product performance is not suitable for commercial applications.
Using high-efficiency mass transfer technology, the iron-containing waste slag is leaching and decomposed and reacted through a high-mix continuous reactor to prepare high-uniformity iron phosphate and lithium iron phosphate. The method includes multi-step processing: leaching, decomposition, reaction, washing, crystallization and heat treatment to ensure uniformity and high performance of the product.
It achieves high uniformity preparation of iron phosphate and lithium iron phosphate, improves the electrochemical performance of the product, especially the cycle stability and capacity performance at high magnification, and is suitable for commercial applications.
Smart Images

Figure CN119637824A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of energy storage material preparation, and in particular to a method for preparing high-uniformity iron phosphate and lithium iron phosphate by utilizing iron-containing waste slag. Background Art
[0002] In recent years, stimulated by global warming, resource depletion and environmental degradation, the demand for green and efficient lithium-ion batteries in electric vehicles (EVs) and energy storage systems has grown exponentially. Olivine-structured lithium iron phosphate has the advantages of abundant natural resources, high safety, long life, low cost and eco-friendliness, and is a promising commercial lithium-ion battery cathode material.
[0003] Lithium iron phosphate cathode materials can be prepared by a variety of processes. Among them, the process of preparing iron phosphate by co-precipitation coupled with carbon thermal reduction at a controllable pH value and temperature using cheap iron and phosphorus sources as raw materials is widely used in industrial production due to its low cost, low energy consumption and in-situ uniform carbon coating. The morphology and size of the precursor FePO4 generated in the co-precipitation step will greatly affect the electrochemical properties of LiFePO4 / C. The overcapacity of low-end iron phosphate in the market and the unstable product quality have led to fluctuations in the product performance of lithium iron phosphate. Therefore, the controllable preparation of iron phosphate is of great significance to the performance improvement of lithium iron phosphate.
[0004] On the other hand, many industrial production processes, including titanium dioxide production, yellow phosphorus production, and the steel industry, will be accompanied by the generation of a large amount of iron-containing bulk industrial waste, which becomes a potential iron ore resource. However, due to the complexity of impurity elements, difficulty in recycling, and low added value, they cannot be fully utilized and are eventually disposed of by accumulation or landfill, resulting in waste of resources and potential environmental pollution. With the implementation of the country's "dual carbon strategy", all walks of life are laying out scientific and technological research on energy conservation and consumption reduction and improving resource utilization, and the basic industries such as steel, petrochemicals, building materials, and energy are unprecedentedly strong. Due to the significant advantages of energy conservation and carbon reduction, green environmental protection in the new energy industry and the policy regulations in the field of energy storage, the lithium iron phosphate market cannot be underestimated, and it has also created unprecedented development opportunities for the high-value utilization of iron-containing waste slag.
[0005] In the existing technology, the technology of high-value utilization of iron-containing waste slag to generate lithium iron phosphate reported so far still has technical bottlenecks. The morphology of the prepared precursor product is uneven and the particle size is large. The lithium iron phosphate prepared in this way inherits the properties of the precursor, with a long lithium ion diffusion path and limited capacity performance, especially serious high-rate attenuation. The product performance is not suitable for commercial applications. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing high-uniformity iron phosphate and lithium iron phosphate, using iron-containing waste slag as the iron source, based on efficient mass transfer technology, the prepared iron phosphate and lithium iron phosphate products have excellent performance, achieve high-value utilization of waste and improve production cost advantages.
[0007] In a first aspect, the present invention provides a method for preparing high-uniformity iron phosphate (FePO4) using iron-containing waste slag, comprising the following steps: S1. After leaching and removing the iron-containing waste slag, an oxidant is added to obtain an iron source solution; after dissolving the phosphorus source, a phosphorus source solution is obtained; S2. Pump the iron source solution and the phosphorus source solution into the two feed ports of the high-mix continuous reactor respectively, control the feed flow rate of the iron source solution and the phosphorus source solution to be 100-800 mL / min, the thickness of the reaction zone to be in the range of 0.1-6 mm, the reactor rotor speed to be 1000-7000 rpm, and the reaction temperature to be 70-120°C; collect the effluent into a stirred reactor; S3 stirring the effluent in the stirred reactor, reacting, then aging, separating the precipitate, washing, grinding, to obtain an iron phosphate intermediate; S4. The ferric phosphate intermediate is crystallized, and then the precipitate is separated, washed, and ground to obtain a powder, which is then heat-treated to obtain the ferric phosphate.
[0008] In step S1 of the present invention, the iron-containing waste slag includes but is not limited to at least one of waste steel slag, vanadium-removing ferro slag, ferrous sulfate, ferrous chloride, ferrous nitrate, ferric sulfate, ferric chloride, and ferric nitrate.
[0009] Iron-containing waste slag contains various other impurity elements, such as sodium, potassium, calcium, magnesium, aluminum, iron, etc. These impurity elements need to be removed when preparing the iron source solution. In the existing method, the iron-containing waste slag is generally first leached with a solvent to leach the iron and impurity elements in the iron-containing waste slag together. Then the leachate is subjected to impurity removal treatment to remove the impurity elements therein. In this method, the impurity removal process of the leachate is complicated and difficult.
[0010] In some embodiments of the present invention, before leaching the Fe element, the iron-containing waste slag is pretreated with a first leaching solvent to selectively leach the impurity elements in the iron-containing waste slag, and then filtered, the filtrate is discarded, and the filter residue is washed with a washing solvent.
[0011] Specifically, during the pretreatment process, different first leaching solvents are selected in turn according to the types of impurity elements in the iron-containing waste slag, and leaching treatment is carried out at different temperatures, so that different impurity elements (sodium, potassium, calcium, magnesium, aluminum, iron, etc.) in the iron-containing waste slag can be selectively separated in turn.
[0012] In the present invention, the first leaching solvent includes at least one of water, acid and alkali; wherein the acid includes at least one of acetic acid, oxalic acid, citric acid, hydrochloric acid, sulfuric acid and nitric acid; the alkali includes at least one of sodium hydroxide solution, potassium hydroxide solution and ammonia water. When the waste residue contains water-soluble salts, such as titanium dioxide waste residue, water can be used as the first leaching solvent to dissolve the soluble salts in the waste residue. The first leaching solution needs to be selected according to the types of impurity elements in the iron-containing waste residue. For example, for waste residue containing aluminum elements, alkali solution can be used for treatment to leach the aluminum elements; for waste residue containing calcium and magnesium elements, acetic acid solution can be used for treatment to leach the calcium and magnesium elements.
[0013] After each leaching, filter and discard the filtrate, and then use a washing solvent to wash the filter residue to remove soluble salts on the surface of the filter residue. Among them, the washing solvent may include at least one of deionized water, ultrapure water, and filtrate. Depending on the type of impurity elements in the iron-containing waste residue, the number of pretreatments may be 0 to 5 times. When ferrous sulfate, ferrous chloride, ferrous nitrate, ferric sulfate, ferric chloride, and ferric nitrate are used as iron sources, no pretreatment is required. After pretreatment, the main impurity elements in the filter residue have been removed, thereby greatly reducing the difficulty of subsequent impurity removal.
[0014] In some embodiments of the present invention, during the pretreatment, the dissolution temperature is controlled to be 20-150°C, for example, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, etc. The solid-liquid mixing ratio is controlled to be 1:2-30, for example, 1:2, 1:4, 1:5, 1:8, 1:10, 1:12, 1:15, 1:20, 1:25, 1:30, etc. The stirring reaction is carried out for 1-10 h, for example, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, etc.
[0015] In step S1 of the present invention, after pretreatment, the cleaned filter residue is mixed with the second leaching solvent to leach the Fe element in the filter residue. Wherein, the second leaching solution is preferably a strong acid, for example, it may include at least one of hydrochloric acid, sulfuric acid, and nitric acid. These strong acids are not only low in price, but also help to improve the leaching rate and rate of the iron element. During the leaching process, the dissolution temperature is controlled to be 20~150°C, for example, it can be 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, etc. The solid-liquid mixing ratio is controlled to be 1: 2~30, for example, it can be 1:2, 1:4, 1:5, 1:8, 1:10, 1:12, 1:15, 1:20, 1:25, 1:30, etc. The reaction is stirred for 1 to 10 h, for example, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, etc.
[0016] After leaching 1 to 3 times, the waste residue is filtered out to obtain a leachate. The leachate is then decontaminated and concentrated, and an oxidant is added to obtain an iron source solution. The concentration is performed by dissolving an iron-containing salt into the solution, including at least one of ferrous sulfate, ferrous chloride, ferrous nitrate, ferric sulfate, ferric chloride, and ferric nitrate; or the solution is evaporated and concentrated. Furthermore, after concentration, the concentration of iron ions in the iron source solution is 0.01 to 3 mol / L. The oxidant includes, but is not limited to, at least one of hydrogen peroxide and peracetic acid.
[0017] Compared with the impurity removal method in the prior art, the present invention first extracts and removes the impurity elements in the iron-containing waste slag through different solvents, and then extracts the iron element, which can greatly simplify the impurity removal process and reduce the difficulty of impurity removal.
[0018] In step S1 of the present invention, when preparing the phosphorus source solution, the phosphorus source is magnetically stirred or mechanically stirred for 5 to 240 min at a temperature of 10 to 90 ° C, ultrasonically treated, and the concentration of phosphate ions in the solution is controlled to be 0.1 to 10 mol / L, and the phosphorus source solution is fully dissolved. Wherein, the stirring temperature can be 10 ° C, 20 ° C, 30 ° C, 40 ° C, 50 ° C, 60 ° C, 70 ° C, 80 ° C, 90 ° C, etc.; the stirring time can be 5 min, 10 min, 20 min, 30 min, 50 min, 80 min, 100 min, 120 min, 200 min, 240 min, etc. The phosphorus source includes but is not limited to at least one of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, ammonium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, and sodium phosphate.
[0019] In step S2 of the present invention, the high-mix continuous reactor is a high-mix continuous rotary reactor disclosed in Chinese patent CN202210606385.0. At a high-flux feed rate, the mixed precipitation of reactants is carried out by a high-mix continuous reactor, and the molecular-level materials can be uniformly mixed before the reaction occurs under high-speed turbulence, shearing and confinement, thereby greatly improving the mass transfer efficiency, improving the high-flux production efficiency, and ensuring the fineness and uniformity of the product; in addition, due to the optimization of the morphology of the reactor, the influence of trace impurities on the performance of iron phosphate and lithium iron phosphate can be offset, so the requirements for the degree of impurity removal can be reduced to a certain extent. The product thus obtained does not require further recrystallization.
[0020] Furthermore, when feeding into the high-mix continuous reactor, the molar ratio of iron to phosphorus in the iron source solution and the phosphorus source solution is controlled to be (0.2~2):1, for example, it can be 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.8:1, 1:1, 1.2:1, 1.5:1, 1.8:1, 2:1, etc.
[0021] Further, in the present invention, the oxidant is first mixed with the iron source solution for pre-oxidation, and then fed with the phosphorus source solution from the feed port of the high-mix continuous reactor. In the reactor, the iron source and the phosphorus source are uniformly metered and mixed. The reaction and oxidation steps are separated to prevent the decomposition of excess hydrogen peroxide to produce a large number of bubbles, which is not conducive to the back mixing of liquid in a narrow reaction area, thereby suppressing the uniformity of supersaturation. The experimental results show that when the reaction and oxidation steps are carried out simultaneously, the average particle size of the product is 3.11 μm, and when the reaction and oxidation steps are separated, the average particle size of the product is 1.91 μm, and the particle size difference is obvious but the tap density of the two is equivalent. This shows that for this reactor, the separation step will be able to better ensure the uniformity of supersaturation, thereby obtaining a uniform product with a small particle size.
[0022] Furthermore, in step S3 of the present invention, it also includes adding a water-soluble polymer auxiliary agent solution to the stirred reactor to assist and strengthen the coprecipitation reaction process. The water-soluble polymer auxiliary agent is pre-dissolved in water, and the mass fraction of the obtained water-soluble polymer auxiliary agent solution is 0.05-5%, for example, it can be 0.05%, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, etc.; the water-soluble polymer auxiliary agent includes but is not limited to at least one of polyacrylamide, polyethylene glycol, polyvinyl alcohol, and polyvinyl pyrrolidone.
[0023] Further, in step S3 of the present invention, when reacting in a stirred reactor, the reaction temperature is preferably controlled to be 20-150°C, for example, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, etc. Further, the initial reaction pH is adjusted to 0.8-1.3, for example, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, etc. Low reaction pH is beneficial to prevent impurity ions from precipitating into the product.
[0024] Further, in step S3 of the present invention, during aging, the aging temperature is preferably controlled to be 20-150°C, for example, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, etc. The aging time is preferably 0.5-48 h, for example, 0.5 h, 1 h, 2 h, 4 h, 8 h, 16 h, 24 h, 32 h, 48 h, etc.
[0025] Furthermore, after aging, solid-liquid separation is performed, unreacted raw materials and reaction by-products are removed by washing with a solvent, vacuum drying is performed, and the mixture is fully dried and ground into powder. Wherein, the temperature of the solvent is 20-50°C, for example, 20°C, 30°C, 40°C, 50°C, etc.; the temperature of vacuum drying is 40-150°C, for example, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, etc.; the time of vacuum drying is 1-48 h, for example, 1 h, 2 h, 4 h, 8 h, 16 h, 24 h, 32 h, 48 h, etc. The method of solid-liquid separation includes, but is not limited to, at least one of decantation, vacuum filtration, centrifugal separation, and gravity sedimentation. When performing solvent washing, the solvent used is at least one of ethanol, deionized water, ultrapure water, acetone, methanol, and chloroform.
[0026] Further, in step S4 of the present invention, during the crystallization treatment, the powder is mixed with a phosphoric acid solution, and the crystallization temperature is controlled to be 20-150°C, for example, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, etc.; the initial crystallization pH is adjusted to 1-5, for example, 1, 2, 3, 4, 5, etc.; and the crystallization is performed for 0.5-48 h, for example, 0.5 h, 1 h, 2 h, 4 h, 8 h, 16 h, 24 h, 32 h, 48 h, etc.
[0027] Further, after the crystallization is completed, the precipitate is separated from the solid and liquid, the filter cake is washed with a solvent and then dried, and then ground and dispersed to obtain the iron phosphate intermediate powder. Wherein, the temperature of the solvent is 20~50℃, for example, it can be 20℃, 30℃, 40℃, 50℃, etc.; the drying temperature is 40~150℃, for example, it can be 40℃, 50℃, 60℃, 70℃, 80℃, 90℃, 100℃, 110℃, 120℃, 130℃, 140℃, 150℃, etc.; the drying time is 1~48h, for example, it can be 1h, 2h, 4h, 8h, 16h, 24h, 32h, 48h, etc. The method of solid-liquid separation includes but is not limited to at least one of decantation, vacuum filtration, centrifugal separation, and gravity sedimentation. When performing solvent washing, the solvent used is at least one of ethanol, deionized water, ultrapure water, acetone, methanol, and chloroform.
[0028] Further, in step S4 of the present invention, the heat treatment can be carried out in a muffle furnace or a tube furnace. Preferably, the heat treatment temperature is controlled to be 500-900 ° C, for example, it can be 500 ° C, 550 ° C, 600 ° C, 650 ° C, 700 ° C, 750 ° C, 800 ° C, 850 ° C, 900 ° C, etc. The heating rate is 1-30 ° C / min, for example, it can be 1 ° C / min, 5 ° C / min, 10 ° C / min, 15 ° C / min, 20 ° C / min, 25 ° C / min, 30 ° C / min, etc. The heat treatment is carried out under a protective atmosphere, and the atmosphere is at least one of air, oxygen, nitrogen, and argon. The constant temperature time is 3-10 h, for example, it can be 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, etc.
[0029] The second aspect of the present invention also provides a method for preparing high-uniformity lithium iron phosphate, comprising the following steps: The lithium source, the carbon source and the iron phosphate precursor are mixed and ground, and then pressed into tablets on a tablet press at a pressure of 15-35 MPa, and then reacted at a constant temperature under a protective atmosphere, with the terminal temperature controlled at 500-900° C. and the constant temperature time being 6-48 hours; after cooling, the mixture is ground, dispersed and sieved to obtain the lithium iron phosphate.
[0030] Wherein, the lithium source includes but is not limited to at least one of lithium carbonate, lithium hydroxide, lithium oxide, lithium acetate, lithium oxalate, and lithium formate; the iron phosphate precursor is high-uniformity iron phosphate prepared by the above method; The carbon source is inorganic carbon, organic carbon, high molecular polymer or natural carbon compound; wherein the inorganic carbon source includes at least one of conductive carbon black, acetylene carbon black, carbon nanoparticles, carbon nanotubes, carbon fibers, graphene, graphene oxide, and graphene composites; the organic carbon source includes at least one of sucrose, glucose, fructose, salicylic acid, acrylic acid, ascorbic acid, urea, oleic acid, citric acid, isohexanoic acid, and cyclodextrin; the high molecular polymer includes at least one of polyethylene glycol, polyaniline, polymethyl methacrylate, polyvinyl alcohol, polyvinyl pyrrolidone, and polypropylene; the natural carbon compound includes at least one of cellulose and starch; Furthermore, during mixing, the Li / Fe molar ratio is controlled to be 0.8-2, for example, the molar ratio can be controlled to be 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, etc.; the amount of carbon source used is a C / Fe molar ratio of 1-6, for example, the molar ratio can be 1, 2, 3, 4, 5, 6, etc.
[0031] Further, the grinding method is dry grinding or wet grinding. Dry grinding uses at least one of a ball mill, a high-pressure roller mill, and a grinder. When a ball mill is used, the rotation speed is 150 to 800 rpm, for example, it can be 150 rpm, 200 rpm, 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm, 800 rpm, etc. Wet grinding uses at least one of a ball mill, a sand mill, and a three-roll mill. The dispersant used in wet grinding is at least one of water, methanol, ethanol, propanol, isopropanol, n-butanol, isobutanol, acetone, butanediol, and dimethylformamide (DMF).
[0032] Furthermore, the ground mixture is dried and then transferred to a tube furnace. The drying method is at least one of forced air drying or vacuum drying, and the drying temperature is controlled to be 50-150°C, for example, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, etc.; the drying time is 1-48 h, for example, 1 h, 2 h, 4 h, 8 h, 16 h, 24 h, 32 h, 48 h, etc.
[0033] Furthermore, the protective atmosphere may be one of nitrogen, argon, and a mixture of argon and hydrogen.
[0034] Furthermore, the isothermal reaction is one of a one-stage type and a two-stage type, which are: a) One-stage method: control the heat treatment temperature to 500~900 ℃, the heating rate to 1~30 ℃ / min, and keep the temperature constant for 0.5~10h.
[0035] b) Two-stage: control the first target temperature to 300~450 ℃, the heating rate to 1~30 ℃ / min, and keep the temperature constant for 0.5~10 h; control the second target temperature to 500~900 ℃, the heating rate to 1~30 ℃ / min, and keep the temperature constant for 0.5~10 h.
[0036] The third aspect of the present invention provides the use of the iron phosphate for the preparation of positive electrode materials, including at least one of lithium iron phosphate and lithium iron manganese iron phosphate positive electrode materials.
[0037] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention uses iron-containing waste slag as raw material, and the iron phosphate intermediate prepared by efficient mass transfer mixing is a flower-shaped micron sheet agglomerate morphology assembled from nanoparticles, and the anhydrous iron phosphate is a porous morphology, which conforms to the crystal structure, does not exist impurities, has a narrow particle size distribution range, has uniform nano primary particles, has good crystallinity, and the volume average particle size D50 of the particles can reach 2.35 μm. In addition, the obtained carbon-coated lithium iron phosphate conforms to the crystal structure, has stable properties, has a porous morphology, a larger specific surface area, uniform carbon coating, uniform primary particles, a large initial charge and discharge specific capacity, excellent rate performance, and good cycle stability.
[0038] 2. The method for preparing iron phosphate and lithium iron phosphate proposed in the present invention is simple and easy to operate, the raw materials are cheap, and the operating process conditions are flexible. It can be applied to the preparation of high-performance precursors and positive electrode materials in actual situations. By changing the reaction conditions and crystallization conditions, the controllable preparation of iron phosphate with different product qualities can be achieved, and then the synthesis of lithium iron phosphate with different performances can be achieved, which is easy to achieve large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a SEM image of the ferric phosphate intermediate prepared using ferrous sulfate heptahydrate as raw material in Example 1.
[0040] Figure 2 This is the XRD diagram of the ferric phosphate intermediate prepared using ferrous sulfate heptahydrate as raw material in Example 1.
[0041] Figure 3 This is a SEM image of anhydrous ferric phosphate prepared using ferrous sulfate heptahydrate as raw material in Example 1.
[0042] Figure 4 This is the XRD diagram of anhydrous ferric phosphate prepared using ferrous sulfate heptahydrate as raw material in Example 1.
[0043] Figure 5 1 is a comparison diagram of XRD patterns of the iron phosphate intermediates prepared in Example 1 (above) and Comparative Example 1 (below).
[0044] Figure 6 This is the XRD diagram of lithium iron phosphate prepared using ferrous sulfate heptahydrate as raw material in Example 2.
[0045] Figure 7 This is a SEM image of lithium iron phosphate prepared using ferrous sulfate heptahydrate as raw material in Example 2.
[0046] Figure 8 This is a TEM image of lithium iron phosphate prepared using ferrous sulfate heptahydrate as raw material in Example 2.
[0047] Fig. 9 This is a graph showing the first charge and discharge performance at 0.1 C of lithium iron phosphate prepared using ferrous sulfate heptahydrate as raw material in Example 2.
[0048] Fig.10 This is a rate discharge performance diagram of the lithium iron phosphate prepared using ferrous sulfate heptahydrate as raw material in Example 2 at 0.1, 0.2, 0.5, 1, 2, 5, and 10 C.
[0049] Fig.11 This is a SEM image of the iron phosphate intermediate prepared using steel slag as raw material in Example 3.
[0050] Fig.12 This is the SEM image of anhydrous ferric phosphate prepared using steel slag as raw material in Example 3.
[0051] Fig.13 The XRD diagrams of the ferric phosphate intermediate and anhydrous ferric phosphate prepared using steel slag as raw material in Example 3.
[0052] Fig.14 This is the XRD diagram of lithium iron phosphate prepared using steel slag as raw material in Example 4.
[0053] Fig.15 This is a SEM image of lithium iron phosphate prepared using steel slag as raw material in Example 4.
[0054] Fig.16 This is a TEM image of lithium iron phosphate prepared using steel slag as raw material in Example 4.
[0055] Fig.17 This is the 0.1 C first charge and discharge performance diagram of the lithium iron phosphate prepared using steel slag as raw material in Example 4.
[0056] Fig.18 This is a rate discharge performance diagram of the lithium iron phosphate prepared using steel slag as raw material in Example 4 at 0.1, 0.2, 0.5, 1, 2, 5, and 10 C. DETAILED DESCRIPTION
[0057] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0058] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0059] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods, and the materials, reagents, etc. used are all available from commercial sources unless otherwise specified.
[0060] Example 1 The embodiment provides a method for preparing ferric phosphate using ferrous sulfate heptahydrate as a raw material, comprising the following steps: S1. Weigh 60 g of solid ferrous sulfate heptahydrate, add 200 ml of deionized water, add 16 ml of 4 mol / L H2SO4 solution, ultrasonicate at 60°C for 1 hour, stir until fully dissolved and mixed, add 25 ml of 30% hydrogen peroxide solution to obtain an iron source solution. Weigh 25 g of solid ammonium dihydrogen phosphate, add 200 ml of deionized water, ultrasonicate at 60°C for 1 hour, stir until fully dissolved and mixed, and obtain a phosphorus source solution.
[0061] S2. The iron source solution and the phosphorus source solution were pumped into a high-speed continuous reactor at a rate of 400 ml / min, respectively. The reaction zone thickness was 0.3 mm, the rotor speed was 3000 rpm, and the reactor temperature was controlled at 90 °C. The slurry formed after mixing was added to the reactor, and 2 mL of 0.5% polyethylene glycol aqueous solution was added to the reactor, and stirring was continued at 300 rpm. After the mixing was completed, the pH value of the slurry in the reactor was adjusted to 1, and the reaction temperature was maintained at 90 °C to continue the reaction and aging for 3 hours; the precipitate was filtered and separated from the liquid, and the precipitate was washed alternately with 1000 mL of 30 °C deionized water and 500 mL of 30 °C ethanol to remove residual salts, and vacuum dried at 80 °C for 24 hours, and ground to obtain powder.
[0062] S3. Add the powder into the reactor and continue the crystallization step. Stir the powder with 250 ml of deionized water to mix thoroughly. Add phosphoric acid solution to adjust the pH to 1.5. Control the crystallization temperature to 90 °C and crystallize for 1 hour. Filter and separate the precipitate from the liquid. Use 1000 ml of 30 °C deionized water and 500 mL of 30 °C ethanol to alternately wash the precipitate to remove residual salt. Vacuum dry at 80 °C for 24 hours and grind to obtain iron phosphate intermediate powder.
[0063] S4. The powder was transferred to a crucible and placed in a muffle furnace for heat treatment. The heat treatment temperature was controlled to be 600 °C, the heating rate was 4 °C / min, and the temperature was kept constant for 4 hours under the atmosphere. The powder was cooled to room temperature with the furnace and ground to obtain the target product, anhydrous iron phosphate.
[0064] The SEM images of the product ferric phosphate intermediate and anhydrous ferric phosphate in this example are shown in Figure 1 and Figure 3 As can be seen from the figure, the ferric phosphate intermediate presents a flower-like aggregate morphology, which is composed of micron sheets assembled from nano primary particles. The obtained anhydrous ferric phosphate has obvious nanopores and presents a porous morphology.
[0065] The XRD patterns of the intermediate ferric phosphate and anhydrous ferric phosphate products of this example are shown in Figure 2 and Figure 4 .
[0066] The chemical formula of the ferric phosphate intermediate can be expressed as FePO4·2H2O, and the chemical formula of anhydrous ferric phosphate can be expressed as FePO4. Figure 4 The two XRD patterns in the figure show that the product has good crystal form, which is highly consistent with the standard structure and does not contain other impurities. The volume average particle size is 2.35 μm.
[0067] Comparative Example 1 Comparative Example 1 provides a method for preparing ferric phosphate using ferrous sulfate heptahydrate as a raw material. The difference between the comparative example 1 and Example 1 is that in step S2, a conventional jacketed reactor is used to mix the iron source solution and the phosphorus source solution, and the other steps are the same.
[0068] Figure 5 The SEM images of the iron phosphate intermediates prepared in Example 1 and Comparative Example 1 are shown. As can be seen from the figure, the uniformity of the morphology and size of the primary particles in the iron phosphate intermediate prepared in Comparative Example 1 is poor, while the uniformity of the iron phosphate intermediate prepared in Example 1 is significantly better. This shows that the use of a high-mix continuous reactor can achieve molecular-level mixing of raw materials, ensuring product fineness and uniformity.
[0069] Example 2 This embodiment provides a method for preparing lithium iron phosphate, comprising the following steps: 23 g of anhydrous iron phosphate prepared in Example 1, 16 g of citric acid and 6 g of lithium carbonate were ball milled and mixed at 300 rpm with ethanol as a dispersant. The resulting mixture was dried, fully dispersed and crushed, and tableted at a pressure of 20 MPa on a tablet press and then transferred to a tube furnace. The drying temperature was controlled to be 80 ° C and the drying time was 24 h. A one-stage reaction was carried out under the protective atmosphere of the tube furnace. The heat treatment temperature was controlled to be 700 ° C, the heating rate was 4 ° C / min, and the temperature was kept constant for 10 hours. After the reaction was completed, it was cooled to room temperature, taken out, ground, dispersed, and sieved to obtain the target product, lithium iron phosphate.
[0070] Figure 6-8 The XRD, SEM and TEM images of the lithium iron phosphate prepared in this embodiment are shown in Figure 1. As can be seen from the figure, the chemical formula of lithium iron phosphate is LiFePO4, the crystallinity is good, there is no impurity phase, and it matches the peak shape of the standard card. The material has a porous morphology and a specific surface area of more than 24 m 2 / g, and the particle surface and gaps are uniformly covered with a carbon film of about 4 nm.
[0071] The lithium iron phosphate prepared in this example is used as the positive electrode material to assemble a 2025 button cell, with a lithium sheet as the negative electrode. The initial charge and discharge performance of the battery is measured at 0.1 C. The results are as follows: Fig. 9 As shown in the figure, it can be seen that the first discharge capacity of the button battery can reach 162 mAh / g.
[0072] The rate performance of button cells was measured at 0.1, 0.2, 0.5, 1, 2, 5, and 10 C. The results are as follows: Fig.10 As shown in the figure, the discharge specific capacities of the button cell at different rates are 162.16, 163.92, 157.49, 153.53, 147.91, 136.34 and 125.36 mAh / g, respectively, which indicates that the lithium iron phosphate material prepared in this embodiment has excellent high rate performance.
[0073] Example 3 This embodiment provides a method for preparing ferric phosphate using steel slag as raw material, comprising the following steps: S1. Mix steel slag powder with 1 M HAc at 90°C with a solid-liquid ratio of 1:20, continue stirring for 1.5 hours, filter to obtain filter residue, wash with acid solution and 1000 mL 90°C deionized water in turn to remove soluble salts in the filter residue. After drying at 80°C for 24 hours, mix with sulfuric acid solution at 20°C, continue stirring for 1 hour, filter to obtain filtrate, evaporate and concentrate the filtrate after impurity removal, add appropriate amount of ferrous sulfate, control the Fe element concentration in the solution to 1 M, add 25 ml 30% hydrogen peroxide solution to obtain iron source solution; weigh 25g of ammonium dihydrogen phosphate solid, add 200 ml deionized water, ultrasonicate at 60°C for 1 hour, stir until fully dissolved and mixed evenly, and obtain phosphorus source solution.
[0074] S2. The iron source solution and the phosphorus source solution were pumped into a high-mix continuous rotary reactor at a rate of 400 mL / min, respectively. The thickness of the reaction zone was 0.3 mm, the rotor speed was 3000 rpm, and the temperature of the reaction zone was controlled at 90°C through a water bath pipeline. The slurry formed after mixing was added to the reactor, and 2 mL of 0.5% polyethylene glycol aqueous solution was added to the reactor, and stirring was continued at 300 rpm. After the mixing was completed, the pH value of the slurry in the reactor was adjusted to 1, and the reaction temperature was maintained at 90°C for further reaction and aging for 3 hours; the precipitate was filtered and separated from the liquid, and the precipitate was washed alternately with 1000 ml of 30°C deionized water and 500 mL of 30°C ethanol to remove residual salt, and vacuum dried at 80°C for 24 hours, and ground to obtain powder.
[0075] S3. Add the powder into the reactor and continue the crystallization step. Stir the powder with 250 ml of deionized water to mix thoroughly. Add phosphoric acid solution to adjust the pH to 1.5. Control the crystallization temperature to 90 °C and crystallize for 1 hour. Filter and separate the precipitate from the liquid. Use 1000 ml of 30 °C deionized water and 500 mL of 30 °C ethanol to alternately wash the precipitate to remove residual salt. Vacuum dry at 80 °C for 24 hours and grind to obtain iron phosphate intermediate powder.
[0076] S4. The powder was transferred to a crucible and placed in a muffle furnace for heat treatment. The heat treatment temperature was controlled to be 600 °C, the heating rate was 4 °C / min, and the temperature was kept constant for 4 hours under the atmosphere. The powder was cooled to room temperature with the furnace and ground to obtain the target product, anhydrous iron phosphate.
[0077] The SEM images of the product ferric phosphate intermediate and anhydrous ferric phosphate in this example are shown in Fig.11 and Fig.12 As can be seen from the figure, the ferric phosphate intermediate prepared in this example presents a flower-like aggregate morphology, which is composed of micron sheets assembled from nano primary particles. The obtained anhydrous ferric phosphate has obvious nanopores and presents a porous morphology.
[0078] The XRD patterns of the intermediate ferric phosphate and anhydrous ferric phosphate products of this example are shown in Fig.13 .
[0079] The chemical formula of the ferric phosphate intermediate can be expressed as FePO4·2H2O, and the chemical formula of anhydrous ferric phosphate can be expressed as FePO4. Fig.13 The two XRD patterns show that the product has good crystal form and is highly consistent with the standard structure. Although steel slag with complex impurity elements is used as raw material, the product does not contain other impurities.
[0080] In this embodiment, during the acetic acid pretreatment, the leaching rate of iron element was 5.18%, the leaching rate of calcium element was 79.88%, and the leaching rate of magnesium element was 61.55%. It can be seen that the pretreatment process can greatly reduce the content of impurity elements, while the loss of iron element is relatively small.
[0081] In the process of leaching iron with sulfuric acid, the leaching rate of iron is 64.83%, the leaching rate of calcium is 2.34%, and the leaching rate of magnesium is 29.26%. It can be seen that calcium is not easy to exist in the form of ions in sulfuric acid solution, but exists in the form of calcium sulfate, which covers the surface of steel slag and hinders the leaching of iron. If there is no pretreatment process using acetic acid, a large amount of calcium sulfate will be produced, affecting the leaching efficiency of iron; on the other hand, the acetic acid leachate of calcium can be used for carbon dioxide capture and acetic acid recovery. In addition, for magnesium, if there is no pretreatment process to separate most of the magnesium, almost all of the magnesium will enter the sulfuric acid leachate, bringing a large number of impurity ions.
[0082] Example 4 This embodiment provides a method for preparing lithium iron phosphate, comprising the following steps: 23 g of anhydrous iron phosphate prepared in Example 3, 16 g of citric acid and 6 g of lithium carbonate were ball milled and mixed at 300 rpm with ethanol as a dispersant. The resulting mixture was dried, fully dispersed and crushed, and tableted at a pressure of 15-35 MPa on a tablet press and then transferred to a tube furnace. The drying temperature was controlled to be 80 ° C and the drying time was 24 h. A one-stage reaction was carried out under the protective atmosphere of the tube furnace. The heat treatment temperature was controlled to be 700 ° C, the heating rate was 4 ° C / min, and the temperature was kept constant for 10 hours. After the reaction was completed, it was cooled to room temperature, taken out, ground, dispersed, and sieved to obtain the target product, lithium iron phosphate.
[0083] Figure 14-16The XRD, SEM and TEM images of the lithium iron phosphate prepared in this embodiment are shown in Figure 1. As can be seen from the figure, the chemical formula of lithium iron phosphate is LiFePO4, the crystallinity is good, there is no impurity phase, and it matches the peak shape of the standard card. The material has a porous morphology, and the particle surface and gaps are evenly coated with a carbon film of about 4 nm.
[0084] The lithium iron phosphate prepared in this example was used as the positive electrode material to assemble a 2025 button cell, with the lithium sheet as the negative electrode. The initial charge and discharge performance of the battery was measured at 0.1 C. The results are as follows: Fig.17 As shown in the figure, the first discharge capacity of the button battery can reach 166.86 mAh / g, and the coulombic efficiency is 99.62%.
[0085] The rate performance of button cells was measured at 0.1, 0.2, 0.5, 1, 2, 5, and 10 C. The results are as follows: Fig.18 As shown in the figure, the discharge specific capacities at different rates are 167.44, 160.07, 155.89, 153.56, 146.08, 133.24 and 119.62 mAh / g respectively.
[0086] From the above test results, it can be seen that the lithium iron phosphate positive electrode material prepared from steel slag has excellent electrochemical performance, especially the small attenuation at high rate.
[0087] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.
Claims
1. A method for preparing high-uniformity ferric phosphate using iron-containing waste slag, characterized in that: The following steps are involved: S1. After leaching and removing the iron-containing waste slag, an oxidant is added to obtain an iron source solution; after dissolving the phosphorus source, a phosphorus source solution is obtained; S2. Pump the iron source solution and the phosphorus source solution into the two feed ports of the high-mix continuous reactor respectively, control the feed flow rate of the iron source solution and the phosphorus source solution to be 100-800 mL / min, the thickness of the reaction zone to be in the range of 0.1-6 mm, the reactor rotor speed to be 1000-7000 rpm, and the reaction temperature to be 70-120°C; collect the effluent into a stirred reactor; S3 stirring the effluent in the stirred reactor, reacting, then aging, separating the precipitate, washing, grinding, to obtain an iron phosphate intermediate; S4. The ferric phosphate intermediate is crystallized, and then the precipitate is separated, washed, and ground to obtain a powder, which is then heat-treated to obtain the ferric phosphate.
2. The method for preparing high-uniformity ferric phosphate using iron-containing waste slag according to claim 1, characterized in that: In step S1, the iron-containing waste slag includes at least one of waste steel slag, vanadium-removing ferro slag, ferrous sulfate, ferrous chloride, ferrous nitrate, ferric sulfate, ferric chloride, and ferric nitrate; The phosphorus source includes at least one of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, ammonium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, and sodium phosphate; The oxidant is at least one of hydrogen peroxide and peracetic acid.
3. The method for preparing high-uniformity ferric phosphate using iron-containing waste slag according to claim 1, characterized in that: In step S1, when preparing the iron source solution, before leaching the Fe element, the iron-containing waste slag is pretreated with a first leaching solvent to selectively leach the impurity elements in the iron-containing waste slag, and then filtered, the filtrate is discarded, and the filter residue is washed with a washing solvent; The number of pretreatments is 0 to 5 times, and the first leaching solvent includes at least one of water, acid solution and alkali solution; wherein the acid solution includes at least one of acetic acid, oxalic acid, citric acid, hydrochloric acid, sulfuric acid and nitric acid; the alkali solution includes at least one of sodium hydroxide solution, potassium hydroxide solution and ammonia water.
4. The method for preparing high-uniformity ferric phosphate using iron-containing waste slag according to claim 3, characterized in that: In step S1, when leaching the Fe element, the cleaned filter residue is mixed with the second leaching solvent, the dissolution temperature is controlled to be 20~150°C, the solid-liquid mixing ratio is 1:2~30, and the reaction is stirred for 1~10 hours; then the waste residue is filtered to obtain a leachate; the leachate is impurity-removed and concentrated to obtain an iron source solution; the second leaching solution includes at least one of hydrochloric acid, sulfuric acid, and nitric acid.
5. The method for preparing high-uniformity ferric phosphate using iron-containing waste slag according to claim 1, characterized in that: In step S2, the high-mix continuous reactor is a high-mix continuous rotating reactor disclosed in Chinese patent CN202210606385.0; The concentration of iron ions in the iron source solution is 0.01-3 mol / L, and the concentration of phosphate ions in the phosphorus source solution is 0.1-10 mol / L; when feeding into the high-mix continuous reactor, the molar ratio of iron to phosphorus in the iron source solution and the phosphorus source solution is controlled to be (0.2-2):
1.
6. The method for preparing high-uniformity ferric phosphate using iron-containing waste slag according to claim 1, characterized in that: Step S3 also includes the step of adding a water-soluble polymer additive solution to the stirred reactor; the mass fraction of the water-soluble polymer additive solution is 0.05-5%; the water-soluble polymer additive includes at least one of polyacrylamide, polyethylene glycol, polyvinyl alcohol, and polyvinyl pyrrolidone.
7. The method for preparing high-uniformity ferric phosphate using iron-containing waste slag according to claim 1, characterized in that: In step S3, when reacting in a stirred reactor, the reaction temperature is controlled to be 20-150° C., and the initial reaction pH is adjusted to be 0.8-1.3; During aging, the aging temperature is controlled at 20~150℃ and the aging time is 0.5~48h.
8. The method for preparing high-uniformity ferric phosphate using iron-containing waste slag according to claim 1, characterized in that: In step S4, during the crystallization treatment, the crystallization temperature is controlled to be 20-150°C, the initial crystallization pH is adjusted to be 1-5, and the crystallization is performed for 0.5-48 hours; During the heat treatment, the heat treatment temperature is controlled to be 500-900°C, the heating rate is 1-30°C / min, and the temperature is kept constant for 3-10 hours under the atmosphere; the atmosphere is at least one of air, oxygen, nitrogen, and argon.
9. A method for preparing high-uniformity lithium iron phosphate, characterized in that: The following steps are involved: The lithium source, the carbon source and the iron phosphate precursor are mixed and ground, and then pressed into tablets on a tablet press at a pressure of 15-35 MPa, and then reacted at a constant temperature under a protective atmosphere, with the terminal temperature controlled at 500-900° C. and the constant temperature time being 6-48 hours; after cooling, the mixture is ground, dispersed and sieved to obtain the lithium iron phosphate; Wherein, the lithium source comprises at least one of lithium carbonate, lithium hydroxide, lithium oxide, lithium acetate, lithium oxalate and lithium formate; the iron phosphate precursor is iron phosphate prepared by the method according to any one of claims 1 to 8; The carbon source is inorganic carbon, organic carbon, high molecular polymer or natural carbon compound; wherein the inorganic carbon source includes at least one of conductive carbon black, acetylene carbon black, carbon nanoparticles, carbon nanotubes, carbon fibers, graphene, graphene oxide, and graphene composites; the organic carbon source includes at least one of sucrose, glucose, fructose, salicylic acid, acrylic acid, ascorbic acid, urea, oleic acid, citric acid, isohexanoic acid, and cyclodextrin; the high molecular polymer includes at least one of polyethylene glycol, polyaniline, polymethyl methacrylate, polyvinyl alcohol, polyvinyl pyrrolidone, and polypropylene; the natural carbon compound includes at least one of cellulose and starch; During mixing, the Li / Fe molar ratio is controlled to be 0.8-2, and the amount of carbon source used is controlled to be a C / Fe molar ratio of 1-6.
10. The preparation method according to claim 9, characterized in that: The isothermal reaction is one of a one-stage isothermal reaction and a two-stage isothermal reaction; the one-stage isothermal reaction is: controlling the heat treatment temperature to 500-900°C, the heating rate to 1-30°C / min, and maintaining the temperature for 0.5-10 h; the two-stage isothermal reaction is: controlling the first target temperature to 300-450°C, the heating rate to 1-30°C / min, and maintaining the temperature for 0.5-10 h; controlling the second target temperature to 500-900°C, the heating rate to 1-30°C / min, and maintaining the temperature for 0.5-10 h.
Citation Information
Patent Citations
High-mixing type continuous rotary reactor and method for preparing aluminum salt lithium adsorbent by using high-mixing type continuous rotary reactor
CN114832762A